Evaluation of the BET Theory for the Characterization of Meso and Microporous MOFs. Issue 11 (16th August 2018) - Ambroz, Filip; Macdonald, Thomas J.; Martis, Vladimir; Parkin, Ivan P.
Abstract: Surface area determination with the Brunauer–Emmett–Teller (BET) method is a widely used characterization technique for metal–organic frameworks (MOFs). Since these materials are highly porous, the use of the BET theory can be problematic. Several researchers have evaluated the BET method to gain insights into the usefulness of the obtained results and interestingly, their findings are not always consistent. In this review, the suitability of the BET method is discussed for MOFs that have a diverse range of pore widths below the diameters of N2 or Ar and above 20 Å. In addition, the surface area of MOFs that are obtained by implementing different approaches, such as grand canonical Monte Carlo simulations, calculations from the crystal structures or based on experimental N2, Ar, or CO2 adsorption isotherms, are compared and evaluated. Inconsistencies in the state‐of‐the‐art are also noted. Based on the current literature, an overview is provided of how the BET method can give useful estimations of the surface areas for the majority of MOFs, but there are some crucial and specific exceptions which are highlighted in this review. Abstract : Applicability of the Brunauer–Emmett– Teller (BET) method : The most widely used characterization technique for metal–organic frameworks (MOFs) is the BET method; however, inadequacies of this technique are often overlooked. Based on the current state‐of‐the‐art, this technique can give useful estimations of MOF surface areas; however, there are important and specific exceptions which are discussed in this review.